0750 Interdisciplinary CPAP Care In Children: Report On A 5-year QI Initiative In A Pediatric Sleep Center. (27th April 2018) - Beck, S E; Xanthopoulos, M S; Menello, M C; Brown, C M; Matthews, E C; Smtih, J; Kreher, G D; Liu, W; Marcus, C L
Abstract: Introduction: Implementation of continuous positive airway pressure (CPAP) in children is difficult due to the interplay of behavioral, familial, technical and medical factors. We developed a CPAP Quality Improvement (QI) Program involving sleep physicians, nurses, psychologists and respiratory therapists to provide expert care and support to improve processes aimed at improving patient care and outcomes in children. Methods: All patients initiated on CPAP in the Sleep Center at Children's Hospital of Philadelphia from 2013-present were managed according to our interdisciplinary practice and reviewed in regular QI meetings. Utilizing a REDCap database and a programmed, automated collection of patient records through the electronic health record, the team prospectively monitored the effects of multiple tests of change in initiation cohorts over time to improve outcome and process measures. Two primary outcome metrics included the percentage of newly initiated CPAP patients returning for follow up office visits and percentage returning for post-CPAP polysomnography. Additional measures included CPAP adherence and hospital admission rates. Results: An average of 35 patients per quarter were initiated on CPAP in the Sleep Center (range 14–51/quarter, total 664). Approximately 10% were inactivated over time due to resolution, transition to adult care, transfer, alternative treatment, or unable to follow up. Four-month follow up visit rate per cohort increased from 33% to 71%, while 12-month follow up rate per cohort was sustained > 85%. Compliance rate of post-CPAP polysomnography increased from 50% to 91% per cohort over time. Average use of CPAP was 250–275 minutes/night/year. Analysis of hospital admission rate showed an average of 20% reduction per cohort following CPAP initiation. Conclusion: A serial QI approach to CPAP care in children was successfully implemented in an interdisciplinary pediatric sleep center leading to improvements in CPAP follow up care and polysomnography. A decrease in hospital admissions was also observed associated with the implementation of interventions. Support (If Any): None.